2019
DOI: 10.18203/2349-2902.isj20192942
|View full text |Cite
|
Sign up to set email alerts
|

Medial versus lateral approache in laparscopic right hemicolectomy

Abstract: Background: Approach to right colon cancer is through open exploration but it has many complication, now laparoscopic right hemicolectomy is an advanced cancer surgery, laparoscopic right hemicolectomy can be done by medial or lateral or combined approach.Methods: This is prospective study carried out on 30 patients admitted to department of surgery in menufia university hospital from September 2016 to September 2018 and all cases have RT colon cancer;  The patients are divided into three groups, 1- group A (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Zhu et al, showed medial approach can significantly retrieve more lymph nodes contrary to the lateral approach 20 . Similar results were also seen in other studies by Elsisi et al, Le Voyer et al, and Chang et al [21][22][23] Table 3 shows that four patients had paralytic ileus postoperatively which was managed conservatively (P=0.9). Similarly, the other post-operative parameters were also comparable.…”
Section: Discussionsupporting
confidence: 88%
“…Zhu et al, showed medial approach can significantly retrieve more lymph nodes contrary to the lateral approach 20 . Similar results were also seen in other studies by Elsisi et al, Le Voyer et al, and Chang et al [21][22][23] Table 3 shows that four patients had paralytic ileus postoperatively which was managed conservatively (P=0.9). Similarly, the other post-operative parameters were also comparable.…”
Section: Discussionsupporting
confidence: 88%